Optimization model for the design of a smart energy infrastructure with electric mobility. Issue 9 (2018) - Bracco, S.; Cancemi, C.; Causa, F.; Longo, M.; Siri, S.
Abstract: The objective of the present paper is the definition of an optimization model for the design of a smart energy infrastructure that integrates photovoltaic fields, electrical storage systems, loads and electric mobility. The optimization model is solved in order to minimize the costs related to the installation and maintenance of power plants, storage systems and electric vehicle charging stations and the costs due to the energy exchanges with the public grid which the district is connected to. The focus is pointed on the possibility to combine the most innovative smart mobility systems, such as electric vehicles and related charging stations, also of vehicle-to-grid type, with renewable energy and storage systems.